DETERMINATION OF NITROGEN IN COAL MACERALS USING ELECTRON MICROPROBE TECHNIQUE-EXPERIMENTAL PROCEDURE - Mastalerz M.; Gurba L.W. (My University, 2001)
This paper discusses nitrogen determination with the Cameca SX50 electron microprobe using PC0 as an analyzing crystal. A set of conditions using differing accelerating voltages, beam currents, beam sizes, and counting times were tested to determine parameters that would give the most reliable nitrogen determination. The results suggest that, for the instrumentation used, 10 kV, current 20 nA, and a counting time of 20 s provides the most reliable nitrogen determination, with a much lower detection limit than the typical concentration of this element in coal. The study demonstrates that the electron microprobe technique can be used to determine the nitrogen content of coal macerals successfully and accurately.
Keywords: NITROGEN IN COAL; ELECTRON MICROPROBE; PC0 CRYSTAL